Marco Malvadi: The Art of Killing Well - Jaine, Tom (Petits Propos Culinaires, 2015)
Marco Malvadi: The Art of Killing Well, translated by Howard Curtis: MacLehose Press, 2014: 192 pp., hardback, £12.99.